Design and Develop a Web-Based Information System For Managing Case Administration At The IKADIN Jakarta Selatan Office - Sulastri, Mega; Bani, Alexius Ulan; Sharyanto, Sharyanto (Journal of Engineering, Technology and Computing (JETCom), 2024)
The management of case administration at the IKADIN South Jakarta office is a crucial aspect in supporting the organization's performance and legal services to the community. Conventional administrative processes often face various challenges, such as difficulties in document tracking, data inaccuracy, and slow communication flow between lawyers and clients. To address these issues, this research aims to design and develop an effective, efficient, and easily accessible web-based case administration information system. This information system is designed to automate various case administration processes, from recording and tracking to reporting, in order to enhance productivity and data accuracy at the IKADIN South Jakarta office. In the system development, software development methods are used, including needs analysis, system design, implementation, as well as system testing and evaluation. The main features of this system include case data management, digital document management, reporting, and notification systems to monitor important deadlines.